2015
DOI: 10.1021/acs.jpcc.5b00890
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/Graphene Hybrid Nanoflowers with Enhanced Electrochemical Performances as Anode for Lithium-Ion Batteries

Abstract: In this work, we studied the synthesis and electrochemical performance of MoS 2 and reduced graphene oxide (rGO) hybrid nanoflowers for use as anode material in lithium ion batteries (LIBs). The morphology and microstructure of the samples were characterized by field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Xray diffraction (XRD) and X-ray photoelectron spectrometry (XPS). Herein, the composite nanoflowers delivered a significant enhanced reversible specific capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 39 publications
4
83
0
Order By: Relevance
“…Such sandwiched MoX 2 :C superstructures have been a hotspot for applications as high-performance electrodes in LIBs, [70,76,81,102,[106][107][108]119] SIBs [111,114] and MIBs. [120,121] The approaches for synthesizing sandwiched MX 2 :C superstructure typically include (i) exfoliation/restacking method by incorporating graphenes or organic molecules that can be easily carbonized upon annealing, [70,121] (ii) hydrothermal/ solvothermal methods with addition of pre-synthesized graphenes and carbon quantum dots that can be intercalated into MX 2 , [102,106,119] and (iii) hydrothermal/solvothermal methods that contain organic molecules, such as glucose, PVP, octylamine, oleic acid, dopamine, CTAB, that can be intercalated and carbonized. [76,108,114] For ) and long cycle life (over 500 cycles).…”
Section: :C Superstructures and Composites For Enhanced Rechargementioning
confidence: 99%
“…Such sandwiched MoX 2 :C superstructures have been a hotspot for applications as high-performance electrodes in LIBs, [70,76,81,102,[106][107][108]119] SIBs [111,114] and MIBs. [120,121] The approaches for synthesizing sandwiched MX 2 :C superstructure typically include (i) exfoliation/restacking method by incorporating graphenes or organic molecules that can be easily carbonized upon annealing, [70,121] (ii) hydrothermal/ solvothermal methods with addition of pre-synthesized graphenes and carbon quantum dots that can be intercalated into MX 2 , [102,106,119] and (iii) hydrothermal/solvothermal methods that contain organic molecules, such as glucose, PVP, octylamine, oleic acid, dopamine, CTAB, that can be intercalated and carbonized. [76,108,114] For ) and long cycle life (over 500 cycles).…”
Section: :C Superstructures and Composites For Enhanced Rechargementioning
confidence: 99%
“…As shown in Figure 4a,b, the adsorption energy (E ad ) of a single Na atom of the ReS 2 system (−0.86 eV) is greater than that for the ReS 2 /graphene system (−1.35 eV). [54,[61][62][63] It is concluded that the unique structure of the new 2D-honeycombed nanosheet significantly boosts the electrochemical performance of 1T′-ReS 2 for SIBs. Moreover, this result is confirmed by the charge density differences.…”
mentioning
confidence: 94%
“…Energy Mater. [54,59,60] Therefore, in a number of studies relating to 2D carbon/TMD or rGO/TMD materials, [54,[61][62][63] the 2D rGO or carbon was simplified into a graphene model in the DFT approach. [54][55][56][57][58] The influence of carbon incorporation on ReS 2 was investigated by DFT, to determine electrical conductivity and Na + adsorption/diffusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the stability of MoS 2 remains constant during continuous charge/discharge phenomena. [90] There are numerous reports for MoS 2 and its composites utilized as anode material for Li-ion batteries. [91][92][93] Consequently, MoS 2 QDs was selected as a surface sensitizer to boost the electrochemical properties of Li 4 Ti 5 O 12 .…”
Section: Electrochemical Lithium Storage Of Mos 2 Qdsmentioning
confidence: 99%